Existence of Continuous Functions That Are One-to-One Almost Everywhere - Izzo, Alexander J. (MATHEMATICA SCANDINAVICA, 2016)
It is shown that given a metric space X and a σ-finite positive regular Borel measure μ on X, there exists a bounded continuous real-valued function on X that is one-to-one on the complement of a set of μ measure zero.